An example of a comprehensive technical and administrative mine closure process on the Urcuit mining site (France) - Lecomte, A.; Charmoille, A.; Laoufa, F.; Rupasinghe, S.; Gombert, P. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
The salt mine of Urcuit is located on the Southwest of France near Bayonne between the Pyrenean piedmont plain and the Adour valley. First mine shafts were sunk at the end of the 19th century. Then, exploitation, which lasted more than a century, consisted to mine out a Triassic salt deposit located between 20 m deep to 200 m. Several solution mining technics have been used creating cavities. Some of which are still opened in underground. Locally in the past, depending on the method of exploitation used and the geological and hydrogeological contexts, subsidence or collapses have been observed at surface. In 2013, the mining operator, according to Mining Code, has initiated studies for mine shutdown and has entrusted Ineris for the realization of all the technical documents of the official report (named DADT). Ineris provided technical and administrative support to the site operator throughout the abandonment process. Thanks to 2-year field investigations, Ineris was able to understand the geological, geotechnical, and hydrogeological contexts of the mining site to assess, on the long term, the stability of the known cavities. Investigations carried out on surface and underground waters showed that dissolution processes are always running on Urcuit site, but their extent and magnitude were greatly reduced, following the end of operations and thanks to the surface works performed. The feedback analysis of the measurements of ground movements and the knowledge of the current state of the cavities (volume, shape, depth) were used to evaluate residual ground movement on the surface. Geomechanical study of cavities stability using numerical modelling and taking account the viscoplastic behaviour of salt has also complemented this evaluation. Thus, the risk assessment for ground movements and the definition of their surface area show that the repercussions almost exclusively concern the perimeter of the operator’s property. Considering this land use, Ineris has proposed innovative and adapted solutions to monitor and secure this complex site. Validated by the mining authorities in mid-2017, these recommendations (cavity pressure monitoring, water quality monitoring, closure of boreholes, etc.) are currently the subject of a second phase of monitoring and work on the site. This paper will describe the results of technical studies conducted on the Urcuit mine to identify risks and, for each one, the mitigation works defined that are currently implemented.